GRID FOLLOWING ROBOT USING EVENT -DRIVEN PROGRAMMING TECHNIQUE AND LED-LDR SENSORS - MD. HASIDIN, NURUL ZAHIDAH (Universiti Teknologi Petronas, 2011)
Grid Trekker is a grid follower robot which is a type of mobile robot that uses line detection for its navigation. The ultimate aim of this project is to build a mobile robot that can maneuver correctly through paths detennined by its user. The mobile robot must be able to maneuver based on grids marked on the floor. Using Parallax Board of Education robotics kit, this project focuses on the sensor assembly using combination of LED and light dependant resistor (LDR) which is simple but effective. Another aim of this project is the program development using event-driven programming. Unlike traditional programming, where the control flow is detennined by the program structure, the control flow of event driven programs is largely driven by external events. The main routine basically reacts to events based on its current state and transition to the next state accordingly, much like a Finite State Machine (FSM). Implemented in PBASIC, this technique was successfully implemented in programming the Grid Trekker.